Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF) directly from positive blood culture flasks allows rapid identification of bloodstream infections in immunosuppressed hosts. Issue 3 (19th May 2015) - Egli, A.; Osthoff, M.; Goldenberger, D.; Halter, J.; Schaub, S.; Steiger, J.; Weisser, M.; Frei, R.
Abstract Introduction In immunosuppressed hosts, rapid identification of microorganisms of bloodstream infections is crucial to ensuring effective antimicrobial therapy. Conventional culture requires up to 72 h from sample collection to pathogen identification. Methods We used the SepsiTyper Kit and matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF; Microflex, Bruker) directly from positive blood culture (BacT/ALERT 3D, FN/FA vials; bioMérieux) in comparison to standard culture methodology (VITEK 2; bioMérieux) for species identification. Results A total of 62 consecutive positive blood cultures from immunosuppressed patients (solid organ or hematopoietic transplant recipients, or with febrile neutropenia) were analyzed. Culture yielded gram‐negative bacteria (GNB) in 27/62 (43.5%) and gram‐positive (GPB) in 35/62 (56.5%) vials. For GNB, the predominant species identified by MALDI‐TOF and confirmed by VITEK were Escherichia coli (16/16 correctly identified) and Enterobacter cloacae (4/4), with a sensitivity and specificity of 92.6% and 100%, respectively. For GPB, predominant species were Staphylococcus aureus (3/3), coagulase‐negative staphylococci (12/24), and Enterococcus faecium (6/6) with a sensitivity of 100%, 60%, and 100%, respectively. The median time from blood collection to species identification was 27.4 h with MALDI‐TOF identification and 46.6 h with conventional methodology. Conclusion Using MALDI‐TOF directly from positive blood cultures allowed a shorter time to identification with high sensitivity and specificity in immunosuppressed patients.